Pacific Asian Business Programs in the United States - Kwok, Chuck C. Y. (Journal of International Business Studies, 1986)
As Pacific Asia becomes increasingly important in the world economy, business programs are needed for preparing students who want to specialize in this region. This study develops a comprehensive listing of Pacific Asian business programs currently available in the U.S. It is found that the programs vary significantly in terms of length, structure and regional focus. Although there are a few programs of this kind available, the number may still be insufficient. The American business schools may need to do more in response to the Pacific challenge.